Evaporation heat transfer of the low GWP alternative refrigerants (R-448A, R-449A, R-455A, R-454C) for R-404A in a microfin tube. (August 2021) - Kim, Cheol-Hwan; Kim, Nae-Hyun
Abstract: The literature survey reveals that the studies on evaporation of an alternative refrigerant for R-404A are lacking. In this study, four R-404A alternative refrigerants - two short term refrigerants (R-448A, R-449A) and two long term refrigerants (R-455A, R-454C) - including R-404A were tested in a 7.0 mm O.D. microfin tube. The tests were conducted changing the mass flux from 90 to 300 kg m −2 s −1, heat flux from 5 to 15 kW m −2 and vapor quality from 0.2 to 0.8. During the test, the saturation temperature was maintained at 10 °C. The heat transfer coefficients of R-404A were higher than those of the alternative refrigerants. However, the difference tended to decrease as the mass flux increased. The higher heat transfer coefficient of R-404A may be due to the smaller temperature glide of R-404A as compared with those of other refrigerants. The microfin / smooth tube heat transfer enhancement ratios of the alternative refrigerants ranged from 1.14 to 1.93. With the mixture correction, pure refrigerant correlations successfully predicted the mixture refrigerant data.